Biochar Addition Decreases the Mobility, Bioavailability, and Phytotoxicity of Potentially Toxic Elements in an Agricultural Contaminated Soil. Issue 13 (20th July 2022) - Abou Jaoude, Lena; Nassif, Nadine; Garau, Giovanni; Darwish, Talal; Castaldi, Paola
ABSTRACT: The implementation of organic amendments, such as biochar and compost, can be an effective and innovative environmental friendly option for the recovery of functionality of soils contaminated by potentially toxic elements (PTE). The aim of this study was therefore to assess the influence of a biochar added at 3% w/w (Bio) and its combination with a municipal solid waste compost (MSWC), on the mobility, bioavailability, and phytotoxicity of several (PTE), As (55 mg·kg −1 ), Sb (84 mg·kg −1 ), Ni (176 mg·kg −1 ) and Cr (214 mg·kg −1 ) present in a contaminated soil (TS). Sequential extraction procedures showed that biochar and its combination with MSWC decreased soil labile PTE, with biochar increasing remarkably their residual fraction compared to TS-soil (+47, 59, 4, and 9% for As, Sb, Cr, and Ni respectively). Amendment addition also favored an increase of the metabolic potential and catabolic versatility of soil microbial communities, as well as soil functionality. Dehydrogenase, β-glucosidase, and urease activities in TS+Bio showed a significant increase (+45, 16, and 21% respectively) with respect to control. Results from a pot experiment showed that all treatments increased the plant yields significantly in the order: Bio>Bio-MSWC>TS (e.g. the shoot length of green bell pepper and wheat grown on Bio increased, respectively, by a factor of 1.8 and 1.2 compared to TS plants). The amendments addition also reduced PTE transfer from root to shoot. Overall, the results obtained indicated that biochar addition at 3% can be an effective environmental friendly strategy for the in situ stabilization of PTE in polluted soils.